Weight-Based Enoxaparin for Venous Thromboembolism in Obesity Gives Similar Anti-Xa Levels to Patients <100 kg, with No Increase in Major Bleeding - Maclachlan, Kylee H.; Stevens, Hannah P.; Tran, Huyen A.; Chunilal, Sanjeev D. (Seminars in Thrombosis and Hemostasis, 2019)
In trials assessing venous thromboembolism (VTE) treatment, obese patients are under-represented or excluded. The main objective of this article is to examine the safety of weight-based enoxaparin dosing in obesity, as assessed by anti-factor Xa (anti-Xa) activity, bleeding, and recurrence. A 5-year retrospective audit of patients with acute VTE, weighing > 100 kg, prescribed enoxaparin 1 mg/kg twice daily, with an anti-Xa level 2 to 6 hours post-dose. The primary outcome was anti-Xa levels, and the secondary outcomes were bleeding and recurrence. Results were compared with patients weighing < 100 kg (n = 64), and obese patients prescribed doses < 1 mg/kg (n = 28). One-hundred sixty-six patients weighing > 100 kg with VTE were identified, with 64 excluded for not fulfilling criteria. The remaining 102 patients had a median weight of 130 kg (range: 105–222 kg). The median peak anti-Xa level was 0.93 U/mL, with 56% of levels being in the proposed therapeutic range (0.5–1.0 U/mL), 40% > 1.0 U/mL, and 4% < 0.5 U/mL. The median anti-Xa levels and distribution were not significantly different between patients > 100 kg and patients < 100 kg, while obese patients prescribed < 1 mg/kg were more frequently subtherapeutic (21%). Regardless of weight, the majority of patients with moderate renal impairment (eGFR 30–59 mL/min) had an anti-Xa level > 1.0 U/mL (61%). In the obese patients, there was no major bleeding or recurrence within 30 days. In comparison, patients weighing < 100 kg, despite similar peak anti-Xa levels, had higher rates of bleeding and recurrence. This was likely due to their older age and comorbidities, particularly renal impairment and cancer. These data support weight-based dosing of enoxaparin in obesity with no maximum dose, ensuring therapeutic drug levels, with anti-Xa levels suggested in obese patients with clinical risk factors for bleeding.
Keywords: heparin; low-molecular-weight; obesity; venous thromboembolism